Logam berat dalam sayuran; kajian kes di tiga pasar utama kawasan Kota Bharu, Kelantan - Abdullah, Amirah Syazana (Universiti Sains Malaysia, 2012)
Heavy metal contamination in vegetables could happen due to various environmental factors. High level of heavy metal contents in vegetables will cause risk to health problem. This study is designed to measure on heavy metal accumulation or content of Cd. Pb, Cu, Mn and Zn in two types of vegetables which are bayam (Amaranthus tricolor) and kangkung (Ipomoea aquatic). The samples were obtained in three main market of Kota Bharu area which are Siti Khadijah Market. Wakaf Che Yeh Market and National Agribusiness Terminal (TEMAN). This research was performed to study on the heavy metal contents in vegetables from the three markets as well as the differences in heavy metal contents of vegetables parts (leaves, stems and roots) at three main markets at Kota Bharu, Kelantan. Heavy metal content was analyzed using atomic absorption spectrophotometer (AAS) after digestion by microwave digestion system. Data were analyzed using SPSS version 18. From the study, heavy metal contents detection from the two vegetables showed Pb < Cd < Cu < Zn < Mn. The results showed that during the six week of studies, the lowest metal contents, Pb with a mean 0.81 ± 0.46 mg/kg and the highest metal contents, Mn with mean 19.65 ± 9.91 mg/kg. There was a difference (p < 0.05) in the metal contents of Pb, Cd, and Cu on the three markets studied. In the metal contents of Mn, Zn and Cu, there are significant difference in the two types of vegetables {bayam and kangkung) studied (p < 0.05). In addition, there is a difference (p < 0.05) in Mn and Zn metal contents in the three of vegetables parts. From this study. Cd content exceeds the maximum permissible limit of Malaysian Food Act 1983 (Act 281). While, the metal content of Pb, Cu and Zn still below the maximum level recommended by FAO/WHO in both types of vegetables studied. In conclusion, the study of soil of vegetables site sources to be done in the further to identify the sources of pollution.